Case Management : En kvalitativ studie om upplevelsen av att samverka mellan organisationer - Wennström, Veronica (2012)
The purpose of this thesis is to investigate how the networking partners of Case Management (CM): social services, parole and open correctional system, clinic for treatment of substance abuse and three health centers in the municipal of Luleå, experience this cooperation.To answer the purpose and the questions of issue, interviews has been carried out, i.e. a qualitative science method, since the purpose is to describe experiences. The collected empirical material is based upon interviews with three individuals as well as three group sessions - in total 12 individuals has been interviewed. These individuals have been selected by Case Management in the municipal of Luleå.The results show that the work with individuals with dual diagnosis is a demanding task and that knowledge as how to meet them in the best way is lacking. The result also shows that most of the interviewed subjects didn’t know how CM is organized and that they only received superficial information of CM’s organization. All of the interviewed agrees to that CM has helped them in their every-day work since they now, through CM, has obtained more background information about individual clients. The results also points out that CM has not participated in common meetings, so called “workplace meetings”, to the same extent as when the activity first started. The result finishes with the interviewed subjects experiences of how cooperation between professions works in general. Critic like that the clients had been released from the psychiatric care before they were finished with their treatment. A common view amongst the interviewed subjects was also that the information from the psychiatric care part of CM was found insufficient.Keywords: Case Management, cooperation, collaboration, integration, obstacle, organization Validerat; 20121127 (global_studentproject_submitter)